Sinus hypoplasia in the cystic fibrosis rat resolves in the absence of chronic infection. Issue 9 (8th June 2017) - Grayson, Jessica; Tipirneni, Kiranya E.; Skinner, Daniel F.; Fort, Matthew; Cho, Do‐Yeon; Zhang, Shaoyan; Prince, Andrew C.; Lim, Dong‐Jin; Mackey, Calvin; Woodworth, Bradford A.
Abstract : Background: Sinus hypoplasia is a hallmark characteristic in cystic fibrosis (CF). Chronic rhinosinusitis (CRS) is nearly universal from a young age, impaired sinus development could be secondary to loss of the cystic fibrosis transmembrane conductance regulator (CFTR) or consequences of chronic infection during maturation. The objective of this study was to assess sinus development relative to overall growth in a novel CF animal model. Methods: Sinus development was evaluated in CFTR −/− and CFTR +/+ rats at 3 stages of development: newborn; 3 weeks; and 16 weeks. Microcomputed tomography (microCT) scanning, cultures, and histology were performed. Three‐dimensional sinus and skull volumes were quantified. Results: At birth, sinus volumes were decreased in CFTR −/− rats compared with wild‐type rats (mean ± SEM: 11.3 ± 0.85 mm 3 vs 14.5 ± 0.73 mm 3 ; p < 0.05), despite similar weights (8.4 ± 0.46 gm vs 8.3 ± 0.51 gm; p = 0.86). CF rat weights declined by 16 weeks (378.4 ± 10.6 gm vs 447.4 ± 15.9 gm; p < 0.05), sinus volume increased similar to wild‐type rats (201.1 ± 3.77 gm vs 203.4 ± 7.13 gm; p = 0.8). The ratio of sinus volume to body weight indicates hypoplasia present at birth (1.37 ± 0.12 vs 1.78 ± 0.11; p < 0.05) and showed an increase compared with CFTR +/+ animals by 16 weeks (0.53 ± 0.02 vs 0.46 ± 0.02; p < 0.05). Rats did not develop histologic evidence of chronic infection. Conclusion: CF rat sinuses are smaller at birth, but develop volumes similar to wild‐type rats with maturation. This suggests that loss of CFTR may confer sinus hypoplasia at birth, but normal development ensues without chronic sinus infection.